Cephalometric studies in different populations by means of Ricketts’ analysis - Menéndez Méndez, Leoncio Vladimir (2008)
This paper develops a revision of four studies of cephalometric analysis did by means of Ricketts analysis method, in population of 30 Peruvian subjects, Navajos Indian group, an American black group, 40 Mexican men, whose information were sent to “Foundation Orthodontic Research” (FOR), material sent by Dr Robert Ricketts to the investigator. These cephalograms show that the different values from the cephalometric analysis made in different racial populations, differ in the 100% of the values, or they defer in some factors, like the interincisive angle, the location of the inferior incisor to the line “A” Pog, the aesthetic line “E”, the location of the point “A” that refers about convexity, as well as some different values in the facial depth; these values have a very important meaning to take into consideration when formulating objectives of treatment, that are going to differ in each racial population, different from the caucasian populations.